BAM 1 and RECEPTOR‐LIKE PROTEIN KINASE 2 constitute a signaling pathway and modulate CLE peptide‐triggered growth inhibition in Arabidopsis root. Issue 4 (17th June 2015) - Shimizu, Noriko; Ishida, Takashi; Yamada, Masashi; Shigenobu, Shuji; Tabata, Ryo; Kinoshita, Atsuko; Yamaguchi, Katsushi; Hasebe, Mitsuyasu; Mitsumasu, Kanako; Sawa, Shinichiro
Summary: Ligand receptor‐based signaling is a means of cell‐to‐cell communication for coordinating developmental and physiological processes in multicellular organisms. In plants, cell‐producing meristems utilize this signaling to regulate their activities and ensure for proper development. Shoot and root systems share common requirements for carrying out this process; however, its molecular basis is largely unclear. It has been suggested that synthetic CLV3/EMBRYO SURROUNDING REGION (CLE) peptide shrinks the root meristem through the actions of CLAVATA2 ( CLV2 ) and the RECEPTOR‐LIKE PROTEIN KINASE 2 ( RPK2 ) pathway in Arabidopsis thaliana . Our genetic screening for mutations that resist CLE peptide signaling in roots determined that BAM1, which is a member of the leucine‐rich repeat receptor‐like kinase (LRR‐RLK) family, is also involved in this pathway. BAM1 is preferentially expressed in the root tip, including the quiescent center and its surrounding stem cells. Our genetic analysis revealed that BAM1 functions together with RPK2. Using coimmunoprecipitation assay, we showed that BAM1 is capable of forming heteromeric complexes with RPK2. These findings suggest that the BAM1 and RPK2 receptors constitute a signaling pathway that modulates cell proliferation in the root meristem and that related molecules are employed in root and shoot meristems.